Pengembangan Lembar Kerja Peserta Didik Berbasis Problem-Based Learning Pada Materi Sistem Gerak Pada Manusia Untuk Siswa UPTD SMP Negeri 3 Gunungsitoli Utara - Samilinda Laia; Toroziduhu Waruwu (Program Studi Pendidikan Biologi - Universitas Nias, 2023)
This study was motivated by observations conducted during the Integrated Field Experience Program at SMP Negeri 3 Gunungsitoli Utara, which revealed limited availability of textbooks, unengaging and unmotivating LKPD, and low student participation, resulting in learning outcomes below the minimum competency criteria in science subjects. This research employed a development approach using the ADDIE model (analysis, design, development, implementation, and evaluation) to assess the feasibility, practicality, and effectiveness of a Problem-Based Learning-based LKPD on the human movement system topic for eighth-grade students. The results indicated that the LKPD achieved a very high level of feasibility based on evaluations by subject matter experts (100%), teachers (98%), language experts (100%), and design experts (100%). The practicality of the LKPD, based on individual, small group, and field trials, reached 85%, categorized as very practical. Its effectiveness was demonstrated by a student learning mastery level of 87%, classified as very high. Therefore, the developed LKPD is considered feasible, practical, and effective for use in science learning.